A modalidade do diálogo competitivo e o desenvolvimento de políticas públicas na infraestrutura rodoviária - Dal Castel, Alcione Roberto (My University, 2022)
The changes in bidding contracts arising from the new Law 14.133/2021 and its possible contribution to the solution of legal impasses in the development of public policies in road infrastructure with the potential use of competitive dialogue to solve these impasses. The work presents the administrative law, the theory on Administrative Contracts, Bidding, Crimes committed in bidding, Analysis of Law 8.987/1995, Analysis of Law 8.666/1993 in relation to Law 14.133/2021, Analysis of Competitive Dialogue, and the presentation of the theory on Road Infrastructure. Analysis if the competitive dialogue regarding the new Bidding Law contributes to improve the negotiations between the public administration and the private sector. This research has as importance to remove the doubts if when making the Laws the Legislative Power is in tune with the reality and the necessity of the negotiations between the companies and the Executive Power. In Administrative Law, the contracts for infrastructure works, the public administration must obey the Bidding Law in order to contract by the lowest price, with better technique and better quality, and according to the competitive dialogue of Law 14.133/21 this modality will contribute to the negotiations between the private sector and the public sector, but there is still a long way to go before small companies can also participate in bidding competitions because of the great demands for economic and financial contributions and the bureaucracy required by law. Law 14.133/21, which also deals with administrative contracts, will replace Law 8.666/93 as of March 31, 2023. The methodology applied to this work is a bibliographical research taken from books, scientific articles, the Federal Constitution, and specific Laws of Administrative Law. [resumo fornecido pelo autor]
As alterações nos contratos de licitações advindos da nova Lei 14.133/2021 e a sua possível contribuição para a solução de impasses jurídicos no desenvolvimento de políticas públicas na infraestrutura rodoviária com o potencial uso do diálogo competitivo para solucionar esses impasses. O trabalho apresenta o direito administrativo, a teoria sobre os Contratos Administrativos, Licitação, Crimes praticados na licitação, Análise da Lei 8.987/1995, Análise da Lei 8.666/1993 em relação à Lei 14.133/2021, Análise do Diálogo Competitivo, e a apresentação da teoria sobre Infraestrutura Rodoviária. Análise se o diálogo competitivo referente à nova Lei das licitações contribui para melhorar as negociações entre a administração pública e o setor privado. Essa pesquisa tem como importância tirarem as dúvidas se ao fazerem as Leis o Poder Legislativo está em sintonia com a realidade e a necessidade das negociações entre as empresas e o Poder Executivo. No Direito Administrativo os contratos de obras de infraestrutura a administração pública deverá obedecer a Lei das licitações com o objetivo de contratar pelo menor preço, com melhor técnica e melhor qualidade, e conforme o diálogo competitivo da Lei 14.133/21 essa modalidade contribuirá para as negociações entre o setor privado e o setor público, mas falta muito ainda para que as empresas de pequeno porte possam também participarem de concorrências de licitações por causa das grandes exigências de aportes econômicos e financeiros e de burocracias que a lei exige. A Lei 14.133/21 que trata também dos contratos administrativos passará a partir de 31 de março de 2023 a substituir o texto da Lei 8.666/93 que perderá a validade na íntegra. A metodologia aplicada referente a esse trabalho é uma pesquisa bibliográfica retirada de livros, artigos científicos, Constituição Federal e Leis especificas do Direito Administrativo. [resumo fornecido pelo autor]
Keywords: Direito; Licitação pública; Direito público; Direito administrativo; Serviço público; Contratos administrativos